2019
DOI: 10.1002/advs.201801531
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo Dynamics of Human Glioblastoma Cells in a Microvasculature‐on‐a‐Chip System Correlates with Tumor Heterogeneity and Subtypes

Abstract: The perivascular niche (PVN) plays an essential role in brain tumor stem‐like cell (BTSC) fate control, tumor invasion, and therapeutic resistance. Here, a microvasculature‐on‐a‐chip system as a PVN model is used to evaluate the ex vivo dynamics of BTSCs from ten glioblastoma patients. BTSCs are found to preferentially localize in the perivascular zone, where they exhibit either the lowest motility, as in quiescent cells, or the highest motility, as in the invasive phenotype, with migration over long distance.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 83 publications
2
75
0
Order By: Relevance
“…All cells except for BCSCs were cultured in DMEM or RPMI medium (Invitrogen) supplemented with 10% fetal bovine serum (FBS; Invitrogen), 100 U ml −1 penicillin and 100 μg ml −1 streptomycin (Invitrogen) in a 37 °C incubator containing 5% CO 2 . Human BCSCs were enriched and cultured as previously described 28,29 . All of the chemicals were purchased from Sigma-Aldrich unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All cells except for BCSCs were cultured in DMEM or RPMI medium (Invitrogen) supplemented with 10% fetal bovine serum (FBS; Invitrogen), 100 U ml −1 penicillin and 100 μg ml −1 streptomycin (Invitrogen) in a 37 °C incubator containing 5% CO 2 . Human BCSCs were enriched and cultured as previously described 28,29 . All of the chemicals were purchased from Sigma-Aldrich unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…We studied the interaction between LAAM TC-CQDs and a large panel of cell cultures, including 27 cancer cell lines of different origin, a side population (SP) of cancer stem-like cells isolated from MDA-MB-231 cells 27 ( Supplementary Fig. 18), 12 patient-derived brain cancer stem cell lines (BCSCs) 28,29 and 18 non-cancerous cell lines. A detailed list of the cells used in this study is provided in Supplementary Table 4.…”
Section: Laam Tc-cqds Selectively Target Cancer Cells In Vitro and Inmentioning
confidence: 99%
“…Yi et al (2019) showed that an organ-on-a-chip GBM model that matched the clinical outcome after concurrent chemoradiation with temozolomide exhibited patient-specific sensitivity against specific drugs combinations. The interaction within the perivascular niche has also been studied using this technology, suggesting that glioma CSCs located around the vasculature and presenting with the lowest motility are most probably of the proneural subtype, and those with the highest invasiveness are most probably classified in the mesenchymal subtype; which further supports the role of the tumor niche on intratumor heterogeneity and consequent treatment response (Xiao Y. et al, 2019). Studies regarding GBM response to magnetic hyperthermia have been also carried out in a similar way (Mamani et al, 2020).…”
Section: Organ-on-a-chipmentioning
confidence: 90%
“…Owing to the significant attention toward modeling of cancer in biomaterials‐based microfluidic platforms, several mechanistic insights have been elucidated (Figure 17). [ 219,460,493–496 ] This knowledge has in turn enabled the screening and development of anticancer drugs and therapeutic agents to target tumor cell proliferation, migration, invasion, and other events occurring during the metastatic cascade. Some important areas in in vitro tumor modeling that merit future consideration include the role of biophysical and hemodynamic forces in regulating tumor dormancy, metastatic recurrence, tumor–immune cell interactions, tumor lymphatic clearance, CSC‐phenotype maintenance, the role of obesity in tumor progression and gut microbiota‐mediated tumor control among others.…”
Section: Modeling Vascular Mechanopathology In Vascularized Microphysmentioning
confidence: 99%